2022
DOI: 10.1038/s41598-022-24690-9
|View full text |Cite
|
Sign up to set email alerts
|

Starter culture-related changes in free amino acids, biogenic amines profile, and antioxidant properties of fermented red beetroot grown in Poland

Abstract: Fermentation of two red beet cultivars (Wodan and Alto) with single-strain starter cultures consisting of selected strains of lactic acid bacteria (LAB) of plant origin (Weissella cibaria KKP2058, Levilactobacillus brevis ZF165) and a multi-strain culture (containing W. cibaria KKP2058, L. brevis ZF165, Lactiplantibacillus plantarum KKP1822, Limosilactobacillus fermentum KKP1820, and Leuconostoc mesenteroides JEIIF) was performed to evaluate their impact on betalains, free amino acids, formation of biogenic am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The results of this study showed that the content of phenolic compounds in the juices obtained during the 7-day fermentation ranged from 524.1 to 766.0 mg GAE-L −1 , depending on the variables. The antioxidant activity measured by the DPPH method was 0.26–0.67 μmol Trolox-mL −1 , depending on the type of raw material, the type of fermentation and the starter cultures used [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of this study showed that the content of phenolic compounds in the juices obtained during the 7-day fermentation ranged from 524.1 to 766.0 mg GAE-L −1 , depending on the variables. The antioxidant activity measured by the DPPH method was 0.26–0.67 μmol Trolox-mL −1 , depending on the type of raw material, the type of fermentation and the starter cultures used [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The range of beneficial biological effects that fermented beetroot juice can have on consumers is directly related to the valuable composition of Beta vulgaris L. and the metabolites produced during the fermentation process. Beetroot and its products are a valuable source of nutrients, such as proteins, carbohydrates, dietary fibres (pectins, oligosaccharides), minerals (iron, magnesium, calcium, potassium, zinc, sodium, phosphorus, copper), vitamin C and B group vitamins (folic acid, B 7 or B 3 ), as well as numerous amino acids, nitrates, and biogenic amines [ 6 , 8 , 9 , 15 ]. They are also known for their significant content of phytochemicals with strong antioxidant properties, including polyphenols and pigment compounds such as carotenoids and betalains [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lyophilization process may alter the availability of free amino acids, which are precursors to biogenic amine formation. The freezing and drying phases could modify the protein structures in food, potentially making amino acids more accessible to decarboxylase enzymes, which could either increase or decrease the formation of biogenic amines depending on the specific conditions and the presence of active enzymes [105,106]. The discrepancy in cadaverine levels between sausages prepared with frozen and lyophilized larvae could stem from the more effective reduction in microbial activity and enzyme deactivation achieved through lyophilization compared to freezing.…”
Section: Biogenic Aminesmentioning
confidence: 99%